1) If the graph of "y=f(x)" is translated "a" units horizontally and "b" units vertically, then the equation of the translated graph is "y-b=f(x-a)."
2) We start with the graph of "y=f(x)." The graph of "g(x)=f(-x)" is the graph of "y=f(x)" reflected in the "y" -axis . How points in graph of "f(x)" become points of new graph "g(x)" ?
Visual effect: flip over the "y" -axis
The graph of "h(x)=3g(x)=3f(-x)" is the graph of "y=g(x)" stretched vertically by "3" units.
How points in graph of "g(x)" become points of new graph "h(x)"?
Visual effect: stretch vertically by "3."
How points in graph of "y=f(x)" become points of new graph "y=3f(-x)"?
Comments
Leave a comment